The mistress of Tall Acre : a novel - Frantz, Laura (Revell, 2015)
In the aftermath of the American Revolution a destitute young woman agrees to a marriage of convenience and becomes Mistress of Tall Acre. But when secrets from her husband's past are revealed, loyalties and ties are torn asunder.